ANALISIS PENGELOLAAN BARANG MILIK DAERAH PADA PEMERINTAH KOTA PALU (studi pada Satuan Kerja Perangkat Daerah Pemerintah Kota Palu) - Nizarwati, Nizarwati (Katalogis, 2018)
Local asset (Fixed assets) are part of elements that must be properly managed in order to generate reliable information in the financial statements. The study ains to determine the management of local asset of the government of Palu City. Data collection menhods include obsernation, interview, dokument, and literature review. Data analysis is descriptive qualitative. The result highlights that the local-ownwd assets in Palu is not managed well during 13 management cycles; this indicates in the process of planning and budgeting, reception, storage and sitribution, usage, administration, and utilization. Dokuments of the local assets s much as 22 documents yet to be finanlized; this affects the management of local-owned property. This candition requires coordination between managers and leaders of govrnmental working units, staff and storage manager (treasurer) in all working units.